Premature morbidity and mortality associated with potentially undiagnosed familial hypercholesterolemia in the general population - Kausik K. Ray; Demetris Pillas; Savvas Hadjiphilippou; Kamlesh Khunti; Sreenivasa Rao Kondapally Seshasai; Antonio J. Vallejo-Vaz; David Neasham; Janet Addison (Elsevier, 2023)
Background: Familial hypercholesterolemia (FH) is common, but underdiagnosed, and few systematic early screening programs exist. Objective: To assess health outcomes among those with a recorded diagnosis of FH and potential cases of FH with no recorded diagnosis. Methods: Retrospective cohort study using the UK Clinical Practice Research Datalink. Records of adults were classified as diagnosed FH (FHCoded), or via accepted algorithms using LDL-C and clinical characteristics as potential FH (FHPotential) or unlikely FH (FHUnlikely) using the DLCN or EUROASPIRE criteria (but no record of FH). Outcomes assessed were premature cardiovascular (CV) events, premature deaths and life expectancy. Results: Among 1,729,046 individuals free from CV events, a record of FHCoded before the age of 40 was 0.3/1000 (IQR 0.3-0.4) and increased with age. Where LDL-C levels were available, 1.8/1000 (IQR 1.6-2.0) could be classified as FHPotential. LDL-C was higher for both FHCoded and FHPotential vs FHUnlikely (185.6 and 216.6 vs 116 mg/dL, respectively, p<0.001). Compared to FHUnlikely both FHCoded and FHPotential cohorts had a higher risk of premature cardiovascular events (both p<0.001) with highest rates among FHCoded. Risk of premature deaths did not differ between FHCoded and FHUnlikely, but was 1.88 (95% CI 1.27-2.78, p = 0.002) for FHPotential vs FHCoded and 2.40 (95% CI 1.57-3.67, p<0.001) for FHPotential vs FHUnlikely. At age 18, the FHPotential cohort had a life expectancy 16 years lower than the FHCoded cohort (p<0.001). Conclusions: Potential cases of FH had a doubling in risk of premature death and a large reduction in life expectancy compared to individuals with a recorded diagnosis of FH. These findings strengthen the critical importance of identifying potential cases of FH early and early treatment.